FURTHERING INJUSTICES AGAINST WOMEN: GENETIC INFORMATION, MORAL OBLIGATIONS, AND GENDER - Melo-Martín, Inmaculada De (Bioethics, 2006)
The purpose of this paper is to show that a decontextualized approach to ethical issues is not just unhelpful for the decision making process of real, situated human beings, but dangerous. This is so, because by neglecting the context in which people make moral decisions we run the risk of reinforcing or furthering injustices against already disadvantaged groups. To show this, I evaluate three moral obligations that our ability to obtain genetic information has made salient: the duty to obtain genetic information about ourselves, the obligation to inform family members about genetic risks and the duty not to reproduce when we know that there is a high risk of transmitting a serious disease or defect. I will argue here that in ignoring the context in which these moral obligations are put into practice, and in particular the situation of women in our society, those who defend these moral duties might be furthering injustices against women.